2018
DOI: 10.1159/000489071
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Long Noncoding RNAs in Female Diabetic Peripheral Neuropathy Patients

Abstract: Background/Aims: Diabetic peripheral neuropathy (DPN) is the most common complication of diabetes mellitus (DM). Because of its controversial pathogenesis, DPN is still not diagnosed or managed properly in most patients. Methods: In this study, human lncRNA microarrays were used to identify the differentially expressed lncRNAs in DM and DPN patients, and some of the discovered lncRNAs were further validated in additional 78 samples by quantitative realtime PCR (qRT-PCR). Results: The microarray analysis identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…lncRNAs are deregulated in diabetic peripheral neuropathy and CRPS [57,137,[174][175][176], and similar to miRNAs, they can be detected in liquid biopsies ( Table 4). The most studied lncRNA in DNP is NONRATT021972 which is up-regulated in the serum and correlates with higher neuropathic pain scores, indicating its potential as a biomarker [137,177].…”
Section: Lncrnas As Possible Signatures For Pain Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNAs are deregulated in diabetic peripheral neuropathy and CRPS [57,137,[174][175][176], and similar to miRNAs, they can be detected in liquid biopsies ( Table 4). The most studied lncRNA in DNP is NONRATT021972 which is up-regulated in the serum and correlates with higher neuropathic pain scores, indicating its potential as a biomarker [137,177].…”
Section: Lncrnas As Possible Signatures For Pain Disordersmentioning
confidence: 99%
“…Another up-regulated ncRNA in Type 2 diabetes mellitus and DNP serum is uc.48+ that is involved in purinergic receptor-mediated responses [74,178]. Amongst 1327 deregulated lncRNAs in the PBMCs of female patients with DNP, MALAT1, H19, PVT1 and MIR143HG could potentially qualify as biomarkers [174]. In female CRPS patients, XIST appears as a promising indicator of poor responsiveness to ketamine [57].…”
Section: Lncrnas As Possible Signatures For Pain Disordersmentioning
confidence: 99%
“…Recent studies have posited that lncRNAs may also become a significant factor in DPN. 4,5,18 One clinical study found that there were 446 and 1327 differentially expressed lncRNAs between DM and DPN patients by the microarray analysis, respectively. Although there are more and more researches on lncRNAs, the specific biological role of most lncRNAs is still unknown.…”
Section: Pathophysiology Of Dpnmentioning
confidence: 99%
“…The KEGG pathway analysis of mRNAs co-expressed by differentially expressed lncRNAs between DM and DPN found that the most widely covered is the MAPK signaling pathway, which may be one of the specific mechanisms of lncRNAs participating in DPN. 4 At the same time, lncRNAs compete to occupy a large number of miRNAs in the cell, buffering and reducing their ability to interfere with the target mRNA like a sponge. Studying these ceRNA relationships has become a breakthrough for studying lncRNAs in DPN.…”
Section: Pathophysiology Of Dpnmentioning
confidence: 99%
See 1 more Smart Citation